Fabrateria Nova, Italien (San Giovanni Incarico, località La Civita, Provinz Frosinone). Sekundäre Anbauten am spätrepublikanischen Tempel A - Fröhlich, Thomas (e-Forschungsberichte des DAI, 2020)
The 2019 campaign in Fabrateria Nova focused on a secondary extension to the late republican Temple A. A further section of the podium wall of the temple itself, a late-antique or post-antique dome oven that had been added to the temple when it was already ruined, and a presumed limestone oven from the 15th or the early 16th century were uncovered, which shows the use of the ancient city as a quarry.